Aquaculture toxicology - Kibenge, Frederick S. B.; Baldisserotto, Bernardo; Chong, Roger (Academic Press, 2021)
Aquaculture Toxicology is an essential resource of practical information that covers mechanisms of toxicity and their responses to toxic agents, including aspects of uptake, metabolism and excretion of toxicants in fish, crustaceans and mollusks. This is a reliable, up-to-date, "all inclusive" reference guide that provides an understanding of toxicology information for the aquaculture industry. Written by respected international experts recognized in specific areas of toxicology, this book covers toxins at the environmental, cellular and molecular levels. It identifies areas where more research is needed to generate more knowledge to support a sustainable aquaculture industry, including pharmaceutical pollutants and microplastics. Presents clinical information for the three major aquatic food animals (fish, crustaceans, and mollusks). Discusses commonly used chemicals in aquaculture and their effects on aquatic animals and the environment. Provides the latest advancements in the field of toxicity to facilitate fisheries and aquaculture research